2013
DOI: 10.1016/j.msea.2012.11.043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alloying on the ordering processes in near-alpha titanium alloys

Abstract: a b s t r a c tThe substructure of near-alpha Ti-Al-Sn-Zr-Mo-Si alloys containing up to 12.5 at% aluminum was studied by transmission electron microscopy (TEM). It was shown that long-range order sections are formed at aging temperatures up to 500 1C in alloys, high in aluminum, and the ordered phase is formed by the nucleation and growth mechanism at 700 1C aging temperatures. Causes of changing the phase transformation mechanism have been discussed, and the relationship between the structure and properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 1 publication
4
18
0
Order By: Relevance
“…Meanwhile, there is a slight decrease in the elongation (El) and the reduction in area (RA). These results are similar to those found in the literature [23][24][25], where the silicide precipitates are considered to lead to an increase in strength and a slight drop in ductility for near α titanium alloys. Singh et al [22] reported that the kinetics of silicide precipitation in Ti-6Al-1.6Zr-3.3Mo-0.3Si (VT9) alloy was faster than in Ti-6Al-5Zr-0.5Mo-0.25Si (IMI685), which was attributed to the higher content of strong β-stabilizing element Mo in the former alloy.…”
Section: Tensile Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, there is a slight decrease in the elongation (El) and the reduction in area (RA). These results are similar to those found in the literature [23][24][25], where the silicide precipitates are considered to lead to an increase in strength and a slight drop in ductility for near α titanium alloys. Singh et al [22] reported that the kinetics of silicide precipitation in Ti-6Al-1.6Zr-3.3Mo-0.3Si (VT9) alloy was faster than in Ti-6Al-5Zr-0.5Mo-0.25Si (IMI685), which was attributed to the higher content of strong β-stabilizing element Mo in the former alloy.…”
Section: Tensile Propertiessupporting
confidence: 91%
“…Meanwhile, there is a slight decrease in the elongation (El) and the reduction in area (RA). These results are similar to those found in the literature [23][24][25], where the silicide precipitates are considered to lead to an increase in strength and a slight drop in ductility for near α titanium alloys. The differences in the tensile properties of the alloys are largely due to their microstructures.…”
Section: Tensile Propertiessupporting
confidence: 91%
“…A certain amount of Si element is added to improve its creep performance at high temperatures [8]. These two factors can easily result in the formation of α 2 (Ti 3 Al) in α phase and precipitation of silicide on the α/β interfaces which are dependent on the content of elements and parameters of heat treatment [9]. Over the past 30 years, numerous studies have been carried out on the heat treatment or terminal exposure of these near α Ti alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The particles of the a 2 -phase block intensely the motion of dislocations and thus promote growth in the creep resistance, but commonly embrittle the alloy. At the same time, it has been shown in [17] that at a relatively low aging temperature an a 2 -phase may form by the mechanism of second-kind phase transformation that yields relatively massive (1 -3 mm) regions with ordered structure. In this case the structure contains antiphase boundaries (Fig.…”
Section: Resultsmentioning
confidence: 99%